Implementation of Product-Based Learning on Welding and Plate Practices II Course Oriented to Infrastructure Needs of the Department of Mechanical Engineering Education UNM - Nur, Hamzah; Aqsha, Ismail; Romadin, Achmad; Ashadi, Ninik Rahayu (Formosa Journal of Sustainable Research, 2024)
Product-Based Learning (PBL) enables students not only to learn theory, but also to be directly involved in the production process of real goods or projects, so that the practicum skills needed in the industry can be formed more optimally. This research method used is mixmethode. The results showed that the implementation of PBL in the Welding and Plate Practice II course has great potential to develop student skills that are relevant to industry needs and support the department's infrastructure. The results of PBL implementation also reached a score of 4,304 with a percentage of 48.3% in the “Excellent” category, proving the effectiveness of this method in successfully supporting students' technical skills. Nevertheless, some obstacles such as limited laboratory facilities and lack of cross-disciplinary collaboration and industry involvement are still a challenge